PENGARUH PENGGUNAAN MODEL PEMBELAJARAN RESOURCE BASED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 064020 - Siregar, Aksha Mulyani; Dahnial, Irfan (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Resource-Based Learning is all forms of learning that involve students in learning resources, either individually or in groups. The purpose of this research is to observe the impact of the application of the Resource-Based Learning model on the learning outcomes of fourth-grade students at SDN 064020 Sunggal in the Pancasila Education subject. The approach used in this research is quantitative, specifically a pre-experimental design with a one-group pretest-posttest design. The population in this study is the fourth-grade students of SDN 064020, with a sample of class IVA students totaling 28 students. Data collection methods include observation and tests. The feasibility of the instruments was examined before use through validity and reliability tests. The test results data were first analyzed descriptively and then followed by hypothesis testing using paired samples statistics. The results of this study indicate that the Resource-Based Learning model has an effect on students' learning outcomes in the Pancasila Education subject. This can be seen from the increase in the average learning outcomes from 47.86 (pretest) to 79.64 (posttest), and this is also reinforced by hypothesis testing which shows rejection of the null hypothesis (Ho). Another impact felt from the implementation of Resource-Based Learning is that students become more active during the learning process and the learning process becomes enjoyable